2017
DOI: 10.1021/acsami.6b12115
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Catalytic Activity of Zn-Containing Magnetic Oxides in a Methanol Synthesis: Identifying the Key Factors

Abstract: A new family of Ni-, Co-, and Cr-doped Zn-containing magnetic oxide nanoparticles (NPs) stabilized by polyphenylquinoxaline (PPQ) and hyperbranched pyridylphenylene polymer (PPP) has been developed. These NPs have been synthesized by thermal decomposition of Zn and doping metal acetylacetonates in the reaction solution of preformed magnetite NPs, resulting in single-crystal NPs with spinel structure. For the PPQ-capped NPs, it was demonstrated that all three types of metal species (Fe, Zn, and a doping metal) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 63 publications
3
24
0
Order By: Relevance
“…Along with PPQ, Pd‐containing magnetite NPs were synthesized in the presence of PPP as capping molecules (Table ). This was motivated by the results of our preceding work on doped Zn‐containing magnetic oxides NPs, where hyperbranched PPP allowed for a much higher catalytic activity . TEM images for PPP stabilized Pd‐containing magnetite NPs presented in Figure S8 (SI) show similar morphology as that in the case of the PPQ NP stabilization (see Figure S4, SI).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Along with PPQ, Pd‐containing magnetite NPs were synthesized in the presence of PPP as capping molecules (Table ). This was motivated by the results of our preceding work on doped Zn‐containing magnetic oxides NPs, where hyperbranched PPP allowed for a much higher catalytic activity . TEM images for PPP stabilized Pd‐containing magnetite NPs presented in Figure S8 (SI) show similar morphology as that in the case of the PPQ NP stabilization (see Figure S4, SI).…”
Section: Resultsmentioning
confidence: 68%
“…The XRD pattern of Pd‐6 (Figure S9, SI) contains typical reflections of magnetite and a full set of reflections of Pd 0 . XPS was not performed because polymer shielded the NP surface and no reliable signal could be obtained …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no ZnO phase was detected in Zn-containing magnetic oxides, although the activities of these catalysts in the methanol synthesis were much higher than those of conventional catalysts. To further enhance the catalytic activity, we studied the influence of such doping metals as Ni, Co, and Cr on the structure of Zn-containing magnetic oxides and their catalytic properties in the methanol synthesis (Baird et al, 2017 ). Two thermally stable capping polymers have been explored: (i) linear PPQ (Singh et al, 1995 ; Keshtov et al, 2001 ) and a hyperbranched pyridylphenylene polymer (PPP) (Kuchkina et al, 2015 ).…”
Section: Iron Oxide Can Become a Reservoir For Catalytic Speciesmentioning
confidence: 99%
“…At low doping metal contents, a significant increase of catalytic activity has been observed (the most pronounced for hyperbranched PPP). In neither case, however, Zn or doping metal formed a separate phase and the Fe 2+ :Fe 3+ atomic ratio of magnetite was preserved, both on the NP surface and in subsurface layers (by X-ray photoelectron spectroscopy, XPS) (Baird et al, 2017 ). XPS also showed that there is a gradient in Zn and doping metal contents with clear surface enrichment.…”
Section: Iron Oxide Can Become a Reservoir For Catalytic Speciesmentioning
confidence: 99%